1931
DOI: 10.1113/jphysiol.1931.sp002742
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exposure to cold on the pulse rate and respiration of man

Abstract: The other confirmatory experiments were carried out at Basel where the string galvanometer was conveniently accessible for counting the pulsea process not always easy when the patient is shivering. There a bed was placed with an ample supply of bed-clothes. Each experiment was divided into three periods.Period I. The subject of the experiment was naked and lay in comfort covered with the bed-clothes until his pulse became steady.Period II. The bed-clothes were then removed. He was exposed for about half an hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1931
1931
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Zhhlava, Sobotka, Reinig & MysliveEek (1961) showed that the removal of the neopallium of the rat resulted in some disturbance to thermoregulation, but this was not of a gross nature. This essentially confirms and extends the observations of Bazett & Penfield (1922), Bazett et al (1933), Pinkston et al (1934), andRioch (1937) that removal of the forebrain in cats and dogs has little effect upon thermoregulation and those of Clark, Magoun & Ranson (19393) who found that damage to the thalamus causes no obvious disturbance to temperature regulation in the cat.…”
Section: Dependence Of Homoeothermy Upon the Integritysupporting
confidence: 89%
“…Zhhlava, Sobotka, Reinig & MysliveEek (1961) showed that the removal of the neopallium of the rat resulted in some disturbance to thermoregulation, but this was not of a gross nature. This essentially confirms and extends the observations of Bazett & Penfield (1922), Bazett et al (1933), Pinkston et al (1934), andRioch (1937) that removal of the forebrain in cats and dogs has little effect upon thermoregulation and those of Clark, Magoun & Ranson (19393) who found that damage to the thalamus causes no obvious disturbance to temperature regulation in the cat.…”
Section: Dependence Of Homoeothermy Upon the Integritysupporting
confidence: 89%
“…shivering) to regulate body temperatures, but does not prevent their activation. Given that skin wetness (Fukazawa & Havenith, ), which occurs subsequent to sweating (Hardy, ), and shivering (Barcroft & Verzar, ) are known to modulate thermal discomfort, it has been proposed that the activation of sweating and shivering in humans may be required inputs for thermal behaviour to be initiated (Schlader, ). On the contrary, our data indicate that sweat rate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it remains unknown whether the activation of shivering or sweating is required for thermal behaviour to be initiated (Schlader, 2014). On the one hand, in hot and cold environments thermal discomfort can be brought about or exacerbated by skin wetness (Fukazawa & Havenith, 2009), which occurs subsequent to sweating (Hardy, 1970), and shivering (Barcroft & Verzar, 1931), respectively. This suggests that there might be a causal role for sweating or shivering in the initiation of thermal behaviour in humans (Schlader, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Changes of Heart Rate in the Still Stirred Unclothed Immersions.-A rise of heart rate in warm, or a fall in cool, surroundings has often been observed [Barcroft and Verzar, 1931;Swift, 1932;Barcroft and Marshall, 1923-24;Bazett, Scott, Maxfield and Blithe, 1937;Cooper and Kerslake, 1955]; the last authors considered that the rapid increase in heart rate after exposure of men to radiant heat indicated that the change was a direct reflex response from the skin and not a result of vasodilatation, but the continuing rise in rate during the present 37 80 C. immersions makes it likely that vasodilatation and perhaps an increase in the temperature of the heart played a part in this case. The men's immediate fall in heart rate in water at 250 C. must have been brought about either by a direct reflex from the skin or indirectly by vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%